Designing A Problem-Based Learning Module of English for Naval Architecture - Antika, Rindilla; Asfina, Risda (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2023)
Being an archipelagic country is an added value in various fields for Indonesia. One way to develop archipelagic potential in Indonesia is to improve the quality of human resources in related fields, one of which is naval architecture. A quality that is no less important is the ability to speak English. This study aimed to design a teaching material in the form of module of English for naval architecture using problem-based learning in order to expose students to real world problems. This research employed Research and Development (R&D) using ADDIE design. The phases of this model were analysis, design, development, implementation, and evaluation. This research was conducted in Politeknik Negeri Bengkalis and involved 50 students of Naval Architecture department. The research subjects were involved in defining the topic needs for the module, implementing the module and evaluating the module. The topic of the module is the ESP (English for Specific Purposes) topic. There are some parts of the module: the first part of the module is module identity; the second part is module component; the third part is module material; and the last part is evaluation. In the evaluation part, problem-based learning is used. This module is expected to contribute to the improvement of naval architecture students’ ability in English and further prepare them for their future work and career.